Malaysia Sebagai Negara Yang Bermazhab: Satu Diskusi Awal - Mohd Azhar Abdullah; Muhammad Lukman Ibrahim; Muhammad Amiri Abdul Ghani; Irwan Mohd Subri (Kolej Universiti Islam Antarabangsa Sultan Ismail Petra (KIAS), 2024)
Non-Indexed Publication